2005
DOI: 10.1248/bpb.28.1752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Domperidone on Human Plasma Levels of Motilin, Somatostatin, Gastrin, Adrenocorticotropic Hormone and Cortisol

Abstract: Domperidone is an antinauseant and gastrokinetic drug which has been reported to be effective for treating functional gastrointestinal disorders such as dyspepsia, gastroesophageal reflux, nausea and vomiting. Domperidone also has recently been evaluated for its clinical usefulness in stress and depression. This medicine has frequently been used in the treatment of chronic hypofunction of the gastrointestinal system. 1,2) Some patients who take this medicine do not have organic diseases such as peptic ulcer, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…It would be interesting to determine what role this additional chemical may have on the upstream regulatory components of the endocrine stress axis such as corticotrophic releasing factor (CRF) or adrenocorticotrophic hormone (ACTH). Interestingly, in humans oral administration of domperidone appeared to reduce plasma concentrations of both ACTH and cortisol (Itoh et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to determine what role this additional chemical may have on the upstream regulatory components of the endocrine stress axis such as corticotrophic releasing factor (CRF) or adrenocorticotrophic hormone (ACTH). Interestingly, in humans oral administration of domperidone appeared to reduce plasma concentrations of both ACTH and cortisol (Itoh et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The peptide hormone GAS is a member of the CCK family of peptides and stimulates gastric acid secretion (Rehfeld, 1981). Changes in gastrointestinal function have attracted attention, particularly the mechanisms responsible for alterations of gastrointestinal hormone induced by stress and depression (Itoh et al, 2005;Katagiri et al, 2006). Following the CUMS procedure, significant elevations in gastric mucosa CCK and serum GAS levels were observed in rats.…”
Section: Figmentioning
confidence: 99%
“…It is reported that it promotes gastric emptying in guinea pigs [25] and is useful in adults with gastroparesis [26] as well as in healthy individuals [27] . Other studies in adults have shown increases in motilin-IS and somatostatin-IS levels following domperidone administration [28] .…”
Section: Discussionmentioning
confidence: 93%